Skeletal age and age verification in youthsport - Malina, R. M. (Sports Medicine, 2011)
Problems with accurate chronological age (CA) reporting occur on a more or less regular basis in youth sports. As a result, there is increasing discussion of age verification. Use of `bone age` or skeletal age (SA) for the purpose of estimating or verifying CA has been used in medicolegal contexts for many years and also in youth sport competitions. This article reviews the concept of SA, and the three most commonly used methods of assessment. Variation in SA within CA groups among male soccer players and female artistic gymnasts is evaluated relative to the use of SA as a tool for verification of CA. Corresponding data for athletes in several other sports are also summarized. Among adolescent males, a significant number of athletes will be identified as older than a CA cutoff because of advanced skeletal maturation when they in fact have a valid CA. SA assessments of soccer players are comparable to MRI assessments of epiphyseal-diaphyseal union of the distal radius in under-17 soccer players. Both protocols indicate a relatively large number of false negatives among youth players aged 15-17 years. Among adolescent females, a significant number of age-eligible artistic gymnasts will be identified as younger than the CA cutoff because of later skeletal maturation when in fact they have a valid CA. There is also the possibility of false positives-identifying gymnasts as younger than the CA cutoff because of late skeletal maturation when they have a valid CA. The risk of false negatives and false positives implies that SA is not a valid indicator of CA.